THE INFLUENCE OF VOCABULARY MASTERY AND GRAMMAR ON STUDENTS' READING COMPREHENSION OF NARRATIVE TEXTS - Ridwan, Revi Nur (ANFA MEDIATAMA, 2024)
This study investigates the influence of vocabulary mastery and grammar on students' reading comprehension of narrative texts among 12th-grade students in Bandung. Using a quantitative approach and ex-post facto design, data were collected through vocabulary tests and grammar surveys from a sample of 60 students selected via stratified proportionate random sampling. The results revealed a significant positive correlation between the independent variables (vocabulary and grammar mastery) and the dependent variable (reading comprehension). The correlation coefficient was 0.864, and the regression equation obtained was Y = -14.070 + 0.135X1 + 0.129X2. The findings indicated that vocabulary mastery contributed 48.2% to reading comprehension, while grammar mastery contributed 33.73%. These results suggest that students with higher levels of vocabulary and grammar proficiency have better comprehension of narrative texts. The study highlights the importance of both vocabulary and grammar in reading comprehension and suggests that educational stakeholders, including teachers, school administrators, and parents, should emphasize the development of these skills. Providing a supportive learning environment, enhancing teaching methods, and supplying appropriate resources can further improve students' language proficiency, leading to better academic outcomes. The research contributes to the understanding of how language skills, specifically vocabulary and grammar, are crucial for reading comprehension in the context of English as a foreign language.